2020
DOI: 10.26618/jed.v5i1.2966
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and Inhibiting Factors of Character Education in Learning Social Studies at Primary Schools

Abstract: The main problem of this study is that the students encounter a moral decadence which requires the  integration  support of character education in learning and anticipates various barriers to the integration of character education in learning. The purpose of this study was to identify various factors supporting and inhibiting character education specifically on social studies learning at primary schools. The research method used descriptive qualitative at SD Inpres 34 Bungung Katammu, Bantaeng Regency. In choo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
8
0
3
Order By: Relevance
“…The findings of this study strengthen research Kanji et al (2020), that the factors in supporting and inhibiting character education consist of two aspects, namely internal and external. Supporting factors include teachers, principals (internal), parents (external), and inhibiting factors include teachers, principals (internal), and parents (external).…”
Section: Supporting and Inhibiting Factors In Developing Charactersupporting
confidence: 81%
“…The findings of this study strengthen research Kanji et al (2020), that the factors in supporting and inhibiting character education consist of two aspects, namely internal and external. Supporting factors include teachers, principals (internal), parents (external), and inhibiting factors include teachers, principals (internal), and parents (external).…”
Section: Supporting and Inhibiting Factors In Developing Charactersupporting
confidence: 81%
“…Madrasahs are always kept to look neat, and learning tools are excellent and very organized. The school's efforts in conditioning learning tools are also supported by the behaviour and actions of students who always place or return learning tools after they are finished using them [14].…”
Section: Resultsmentioning
confidence: 99%
“…Other educational and religious activities can be facilitated by the existence of the mosque (Nurhadi, 2019) The present study found that there were some inhibiting factors for the method implementation. Teaching and learning activities always have their inhibiting factors and it can be external and internal factors (Kanji et al, 2020) They should be taken into consideration by the teachers. Students varied background may bring different students' achievement.…”
Section: The Success Rate Of the Methods Implementationmentioning
confidence: 99%